Secure Key Distribution Strategy in OFDM-PON by Utilizing the Redundancy of Training Symbol and Digital Chaos Technique - Shanshan Li; Mengfan Cheng; Lei Deng; Songnian Fu; Minming Zhang; Ming Tang; Ping Shum; Deming Liu (IEEE Photonics Journal, 2018)
A secure key distribution scheme for orthogonal frequency division multiplexing (OFDM) passive optical network system is proposed and experimentally demonstrated. The training symbol (TS), which is used for time synchronization and channel estimation, is formed by adopting a noise-like chaotic sequence. The redundancy of the TS is utilized to embed secure keys. An experiment is performed, in which 7.64 Gb/s 16-quadrature-amplitude-modulation OFDM data and 28.4 Mb/s keys embedded in are successfully transmitted over 25 km standard single mode fiber. The results indicate a promising key distribution method for physical layer secure optical communication.